The risks arising at execution and the termination of legal relationship in the field of town-planning activity - A. I. Yakovleva (Путеводитель предпринимателя, 2020)
On the basis of the analysis of the acting federal and regional legislation, and also jurisprudence the risks arising at execution and the termination oflegal relationship in the field of town-planning activity are classified by cases of town-planning disputes and also problems of protection of the rights of citizens are shown, at implementation of so-called dot building.